Job satisfaction of professionals and paraprofessionals in Agricultural Libraries in Sri Lanka - Wijeweera, K.G.G. (DEGREE OF MASTER IN LIBRARY AND INFORMATION SCIENCE, 2002)
Agriculture is one of the main income sources in Sri Lanka. Agriculture libraries play a major role in the development of agriculture. For an efficient service from libraries job satisfaction of library employees is compulsory. This study investigates whether the main cause for recent resignations of professionals and paraprofessionals in agriculture libraries is job dissatisfaction. The aim of the study is to investigate the level of job satisfaction of library employees in Sri Lanka. Structured questionnaires and interviews were used to gather extensive data about the job satisfaction of library personnel. Thirty agriculture libraries who are members of the Council for Agricultural Research Policy (CARP) were the target groups No sampling procedure was adopted, since the total population was small. Fifteen variables related to the profession and job content were identified. Collected data were presented in the form of tables and graphs. These data were analyzed using percentages, frequencies, six step Likert scale and 2-tailed t-test. The study revealed that majority of professionals and paraprofessionals prefer to work in the same library they are working. It also revealed that there is a less trend of leaving the service of the libraries when the employees are becoming old. The females are more attracted to library profession than males. A large number of personnel attached to agriculture libraries are dissatisfied with regard to the operating procedure. Their satisfaction for other variables is above the average satisfaction level.